2022
DOI: 10.3390/nu14061240
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Cholesterol and the Risk of Rheumatoid Arthritis: A Prospective Study in a Chinese Cohort

Abstract: Objective: This study aimed to investigate whether low-density lipoprotein cholesterol (LDL-C) concentration was associated with the risk of rheumatoid arthritis (RA) in Chinese adults. Methods: The study included the 97,411 participants in the Kailuan Study without RA, with complete baseline LDL-C data, and who did not use lipid-lowering medications at baseline or during follow-up. We used Cox proportional hazards modeling to calculate the hazard ratio (HR) and 95% confidence interval (95% CI) of RA according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Therefore, medical workers should pay attention to evaluate the overall impact of elevated blood lipid levels on cardiovascular risk in elderly patients with RA complicated with anemia due to the control of inflammation. It is suggested that blood lipids and inflammatory indexes in elderly RA patients should be monitored regularly, and corrective measures should be taken in time when the baseline blood lipid levels decrease significantly, so as to avoid further deterioration of the RA and anemia [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, medical workers should pay attention to evaluate the overall impact of elevated blood lipid levels on cardiovascular risk in elderly patients with RA complicated with anemia due to the control of inflammation. It is suggested that blood lipids and inflammatory indexes in elderly RA patients should be monitored regularly, and corrective measures should be taken in time when the baseline blood lipid levels decrease significantly, so as to avoid further deterioration of the RA and anemia [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the previously published articles and relevant clinical experience ( 23 ), the confounding factors that may affect the relationship between dietary live microbes and arthritis were controlled. The main covariates are as follows: Age is categorized into two groups: < 60 years old, and 60 years old and above.…”
Section: Methodsmentioning
confidence: 99%
“…To control for potential confounders, we included the following covariates:Age[18], Gender [2], Ethnicity [2], Education [19], Income [2], Smoke [20], Alcohol [21,22], BMI [23], Hypertension [24], High Cholesterol [25], bloodglucose [26]. These confounders were chosen to consider possible associations with the prevalence of RA.…”
Section: Other Covariates Used In Nhanesmentioning
confidence: 99%